2001
DOI: 10.1017/s0033822200041175
|View full text |Cite
|
Sign up to set email alerts
|

A Recent History of 14C, 137Cs, 210Pb, and 241Am Accumulation at Two Irish Peat Bog Sites: an East Versus West Coast Comparison

Abstract: Data on radiocarbon (14C), 137Cs, 210Pb, and 241Am levels in an ombrotrophic peat sequence from a montane site on the east coast of Ireland are compared with data from a similar sequence at an Atlantic peatland site on the west coast. The 14C profiles from the west and east coasts show a broadly similar pattern. Levels increase from 100 pMC or less in the deepest horizons examined, to peak values at the west and east coast sites of 117 ± 0.6 pMC and 132 ± 0.7 pMC, respectively (corresponding to maximal fallout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
10
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 18 publications
7
10
1
Order By: Relevance
“…55 cm) from the 1986 Chernobyl nuclear accident. Application of the CRS calculation also showed that sediment accumulation rates were extremely high and constant (5.4 cm yr 21 ), consistent with prior radioisotopic analysis of this coring site (Gallagher 2003). As a consequence of such high sedimentation rates, the 330-cm core encompassed a 62-yr period with annual resolution of fossil records.…”
Section: Resultssupporting
confidence: 79%
“…55 cm) from the 1986 Chernobyl nuclear accident. Application of the CRS calculation also showed that sediment accumulation rates were extremely high and constant (5.4 cm yr 21 ), consistent with prior radioisotopic analysis of this coring site (Gallagher 2003). As a consequence of such high sedimentation rates, the 330-cm core encompassed a 62-yr period with annual resolution of fossil records.…”
Section: Resultssupporting
confidence: 79%
“…However, the 137 Cs activity has been detected especially in the upper part of profile, suggesting a possible influence of plant uptake, and until 36 cm of depth, corresponding to the first years of the XIX century, underling a significant downward movement of this radionuclide along the profile. This vertical migration is consistent with the 137 Cs profile reported in another core (2H) from the same site by Zaccone et al (2007c) and in other Irish peat bogs by several Authors (Mitchell et al 1992;Gallagher et al 2001;Coggins et al 2006).…”
Section: Coppersupporting
confidence: 91%
“…2b.) was found to be the least mobile among the investigated radi-248 onuclides, in agreement with findings of other studies (Gallagher et al, 2016). It was present 249 at much lower activities and it was detectable only in few samples.…”
Section: Radionuclide Chronology Reconstruction 226supporting
confidence: 89%